Emerging precarity among international students in Singapore: experiences, understandings and responses. Issue 20 (16th December 2021) - Chacko, Elizabeth
ABSTRACT: In this paper, I explore precarity as experienced by international students studying in the honours college of a public university in the city–state of Singapore. Precarity for this group emanates from the intersection of their temporary migrant status, the country's changing immigration and economic development policies and public opinion about international students in the country. Through interviews and focus group discussions, I examine the life trajectories and aspirations of this group, how they cope with precarity and the strategies they used to minimise their perceived precariousness. I use the term 'emerging precarity' to underscore the temporal nature of students' precarity that arises as they are about to graduate. At this juncture, precarity is heightened by the removal of resources, the ending of their visa status as students and changing policies regarding their ability to stay on and work in the country after earning a degree. Students in this study found ways to counter the effects of precarity and underscore their potential as future workers, long-term residents and possibly future citizens by building their store of human capital and asserting that their understanding of Singaporean values and cultures made them 'locals', on par with the native-born in the workplace.